Model Pembelajaran Mahārah al-Kalām dengan Pendekatan Komunikatif di Madrasah Aliyah - Bakri, Akhmad Shaiful (Aphorisme: Journal of Arabic Language, Literature, and Education, 2022)
Learning Arabic should be comfortable and enjoyable. A study stated that a person's ability to use language in communication is one of the main foundations of success. But in fact, learning Arabic to this day is still not optimal because teachers do not provide opportunities for students to communicate using Arabic in learning actively. The communicative approach is used in realizing the success of learning Mahārah al-Kalām Arabic. Madrasah Aliyah an-Nawawi has a special religious class program that makes students communicative in Arabic. The method used was descriptive qualitative, with 3 Arabic teachers as research subjects and 48 students in class XI MAPK 1-2 as objects. The factors influencing it are teachers, methods, students, modules (learning materials), and madrasah policy leaders. This study concluded that learning Arabic with a communicative approach in class XI MAPK MA an-Nawawi Berjan emphasized the active aspects of students in speaking directly and spontaneously by consistently adding new mufradat and practicing them when using the language.